2015
DOI: 10.1016/j.joca.2015.03.002
|View full text |Cite
|
Sign up to set email alerts
|

OARSI Clinical Trials Recommendations: Soluble biomarker assessments in clinical trials in osteoarthritis

Abstract: Objective To describe requirements for inclusion of soluble biomarkers in osteoarthritis (OA) clinical trials and progress toward OA-related biomarker qualification. Methods The Guidelines for Biomarkers Working Group, representing experts in the field of OA biomarker research from both academia and industry, convened to discuss issues related to soluble biomarkers and to make recommendations for their use in OA clinical trials based on current knowledge and anticipated benefits. Results This document summ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
72
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(76 citation statements)
references
References 47 publications
(69 reference statements)
0
72
0
3
Order By: Relevance
“…This finding suggested that TGF-α/CCL2 is an important promoter of articular cartilage degradation in posttraumatic OA. 26 In another study, oral administration of a high dose of BIS076 (245 mg/kg), a natural porcine cartilage extract associated with hydroxyapatite and vitamin D 3 , reduced serum levels of CTX-II and COMP, as well as MMP-3 in OVX and ACLT rats. 27 In ovariectomized (OVX) rats, serum COMP level was decreased by a combination of estrogen and progesterone hormones 10 weeks after OVX surgery.…”
Section: Ratsmentioning
confidence: 97%
See 2 more Smart Citations
“…This finding suggested that TGF-α/CCL2 is an important promoter of articular cartilage degradation in posttraumatic OA. 26 In another study, oral administration of a high dose of BIS076 (245 mg/kg), a natural porcine cartilage extract associated with hydroxyapatite and vitamin D 3 , reduced serum levels of CTX-II and COMP, as well as MMP-3 in OVX and ACLT rats. 27 In ovariectomized (OVX) rats, serum COMP level was decreased by a combination of estrogen and progesterone hormones 10 weeks after OVX surgery.…”
Section: Ratsmentioning
confidence: 97%
“…in the development and testing of new drugs to advance decision making on dosing, time and treatment effect, trial design, and risk/benefit analysis. 3 …”
Section: Efficacy Of Interventionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study, which included 291 white patients with OA of the knee, it was found a significant increase in blood COMP levels in patients with K-L and consistent with the patient's score [18]. In 324 postmenopausal women, the study showed that the level of II CTX in different parts of OA was different, which suggested that OA can be identified in different parts of the patient [25]. Deficiencies and shortcomings of this study are as follows: firstly, the sample sizes were small, future studies should further expand the number of osteoarthritis patients to further study the possibility of miRNA98b as an early diagnosis of osteoarthritis.…”
Section: Study On the Clinical Value Of Mirna98b As A Potential Biomamentioning
confidence: 88%
“…There is significant interest in developing biochemical markers that can be used to measure the effects of interventions for knee OA on joint tissues 22 . In the present study, two potential markers of joint tissue inflammation (C1M and C3M) decreased over the course of an 18-month clinical trial in overweight and obese adults with knee OA assigned to dietary-induced weight loss or exercise plus weight loss interventions compared to an exercise without diet intervention that served as a control group.…”
Section: Discussionmentioning
confidence: 99%